Penerapan Job Order Costing Dalam Perhitungan Harga Pokok Produksi Pada PT “X” Di Surabaya - Diana Zuhroh; Wiratna Wiratna; Tjandra Wasesa; Heri Toni; Sutini Sutini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This research was conducted to understand how to calculate the correct cost of production at PT "X" using the Job Order Costing method. Calculation of the cost of production is important for companies because it determines the selling price of the product.The research method uses a qualitative type with a qualitative descriptive approach. Data collection techniques include interviews with related parties and direct documentation of the object being researched.The research results show that there is a difference in the calculation of the cost of production made by PT "X" and that carried out by researchers based on job order costing. The differences occurred due to errors in the classification and calculation of factory overhead costs carried out by PT "X", where there were several components of factory overhead costs that had not been included in the calculation, so the results of the calculation of the cost of production at PT "X" were understated than they should be.